Dual-regulation charge separation strategy with the synergistic effect of 1D/0D heterostructure and inserted ferroelectric layer for boosting photoelectrochemical water oxidation. Issue 12 (26th February 2021) - He, Yanfang; Zhu, Jianfei; Yuan, Youwen; Li, Ming; Yang, Ying; Liu, Yuan; Chen, Mingming; Cao, Dawei; Yan, Xiaohong
Abstract : A dual-regulation charge separation strategy with synergistic effect between a 1D/0D heterostructure and inserted ferroelectric layer in TiO2 /SrTiO3 /CdS composite photoanode is developed to boost the PEC performance of TiO2 . Abstract : The poor visible light utilization and inferior charge separation efficiency of the TiO2 photoanode restrict its photoelectrochemical (PEC) activity for water oxidation. Therefore, herein, we report a dual-regulation charge separation strategy with a synergistic effect between a 1D/0D heterostructure and inserted ferroelectric layer in a TiO2 /SrTiO3 /CdS (nanorod/ferroelectric/quantum dot) composite photoanode to boost the PEC performance of TiO2 . The ferroelectric SrTiO3 (STO) nanolayer exhibited a polar charge-induced electric field from the STO/CdS interface toward the TiO2 /STO interface, resulting from strong and endurable spontaneous polarization. The polar charge-induced electric field, assisted by the TiO2 /STO/CdS ternary heterojunction with cascade energy band alignment, simultaneously endowed persistent and rapid charge separation in the bulk and at TiO2 /STO/CdS interfaces, which enhanced the charge separation efficiency by 148% compared to that of pure TiO2 . Meanwhile, the obtained TiO2 /STO/CdS photoanode allowed the integration of boosted charge carrier density, easier hole extraction and increased active sites from the outer CdS 0D quantum dots. Consequently, the TiO2 /STO/CdS photoanode presented a prominently improved photocurrent of 1.85 mA cm −2 (at 1.23 V vs. RHE), which was 7.4 times that of TiO2 . Thus, this integrated regulation strategy may open an avenue to pursue enhanced charge separation assisted by broadened light absorption for converting solar energy into fuel.